2022
DOI: 10.1128/jvi.00475-22
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Herpes Simplex Virus Reactivation Involves a Dual Leucine Zipper Kinase-Dependent Wave of Lytic Gene Expression That Is Independent of Histone Demethylase Activity and Viral Genome Synthesis

Abstract: Reactivation of herpes simplex virus from a latent infection is associated with clinical disease. To develop new therapeutics that prevent reactivation, it is important to understand how viral gene expression initiates following a reactivation stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…However, during the productive replication cycle, the VP16 gene is expressed with late kinetics. During Phase I, VP16, like other late genes, is expressed in the absence of viral DNA replication 33,36,37 . Further, work from the Sawtell and Thompson labs has shown that elements within the VP16 promoter can function prior to immediate-early gene expression, specifically in neurons, and are involved in the initial depression of viral gene expression during acute infection of the ganglia 55,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the productive replication cycle, the VP16 gene is expressed with late kinetics. During Phase I, VP16, like other late genes, is expressed in the absence of viral DNA replication 33,36,37 . Further, work from the Sawtell and Thompson labs has shown that elements within the VP16 promoter can function prior to immediate-early gene expression, specifically in neurons, and are involved in the initial depression of viral gene expression during acute infection of the ganglia 55,65 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of DLK and its downstream mediator JNK are critical steps in reactivation associated with numerous triggers in vitro and ex vivo 32,34,36,37,50 . We therefore tested whether DMXAA-induced reactivation was DLK-dependent; we focused on DMXAA as this gave the most robust reactivation.…”
Section: Innate Immune Activation Promotes Lytic Gene Expression Duri...mentioning
confidence: 99%
“…[46] The reactivation of latent neuronal herpes simplex virus (HSV) infections can cause, besides blisters and sores, severe encephalitis, and it is triggered by neuronal stress. By inducing the initial wave of the increased expression of lytic genes, DLK mediates the reactivation of latent HSV infection in different model systems [37,39,47]. In addition, an association of DLK with different kinds of cancer was found, whereby DLK mRNA expression was positively correlated with lung adenocarcinoma, pancreatic duct adenocarcinoma, sarcoma, and thymoma.…”
Section: Mouse Primary Rgcsmentioning
confidence: 99%
“…Samples were collected at specified hours post infection (h.p.i.). For latent infection, 6-week-old female CD-1 mice (Charles River) were anesthetized by intraperitoneal injection of ketamine hydrochloride (80 mg/kg of body weight) and xylazine hydrochloride (10 mg/kg) and inoculated with 1.5 × 10^6 PFU/eye of KOS strain HSV-1 (in a 5-μL volume) onto scarified corneas, as described previously (58). Mice were housed in accordance with institutional and National Institutes of Health guidelines on the care and use of animals in research, and all procedures were approved by the Institutional Animal Care and Use Committee of the University of Virginia.…”
Section: Cells Viruses Infection and Plasmidsmentioning
confidence: 99%